Epoetin-alfa-induced osteogenesis in the bone organoid model - Natalia A. Nadezhdina; Oleg S. Gudyrev; Sergey V. Nadezhdin; Lyudmila M. Danilenko; Aleksandr A. Dolzhikov; Kristina K. Kremleva; Tatyana G. Pokrovskaya (Research Results in Pharmacology)
Introduction: Erythropoietin interacts ETwith EPOR/βcR(CD131) and activates the non-canonical pathway JAK/STAT and PI3K/AKT. Phosphorylated STAT subunits were found to get dimerized and translocated into the nucleus to activate the expression of the Runx-2 and TGF-β genes. The purpose of the study was to evaluate the effectiveness of osteogenesis when using epoetin alpha as an osteoinducer in an experimental model of a bone organoid.